Does optimal access to dental care counteract the oral health‐related quality of life social gradient?. (December 2016) - Crocombe, LA; Mahoney, GD
Abstract: Background: The aim of this study was to determine if an oral health‐related quality of life (OHRQoL) social gradient existed when Australian Defence Force (ADF) members have universal and optimal access to dental care. Methods: A nominal roll included 4089 individuals who were deployed to the Solomon Islands as part of Operation ANODE and a comparison group of 4092 ADF personnel frequency matched to the deployed group on gender, age group and service type, from which 500 deployed and 500 comparison individuals were randomly selected. The dependent variables were the OHIP‐14 summary measures. Rank was used to determine socioeconomic status. The demographic variables selected were: gender and age. Results: The response rate was 44%. Of the individual OHIP‐14 items, being self‐conscious, painful aching and having discomfort when eating were the most common problems. Mean OHIP‐14 severity was 2.8. In bivariate analysis, there was not a significant difference in mean OHIP‐14 severity (p = 0.52) or frequency of OHIP‐14 impacts (p = 0.57) by military rank. There was a significant increasing OHIP‐14 extent score from commissioned officer to non‐commissioned officer to other ranks (0.07, 0.19, 0.40, p = 0.03). Conclusions: Even with optimal access to dental care, there was an OHRQoL social gradient between military ranks in the ADF.